Investigations on the role of various hemato-biochemical parameters on genital prolapse of cows - Sharma, Vivek; Kumar, Pravesh; Sharma, Akshay; Singh, Madhumeet (The Indian Journal of Animal Sciences, 2022)
The present study was designed for investigation on etiologies of genital prolapse in cattle of Himachal Pradesh. A total of 111 cattle were part of study, 39 were suffering with genital prolapse in pregnant, post-partum and non-pregnant stages of gestation while the remaining 72 cows were in normal pregnancy, post-partum and non-pregnant stage. Blood samples were collected for hormonal (cortisol, estrogen and progesterone), minerals (calcium, phosphorus and magnesium) and biochemical (glucose, total protein, triglycerides, urea, cholesterol, SGPT, SGOT) estimations. Mean plasma estradiol-17Î² elevation was significant (P